Light Harvesting: Near‐Infrared Harvesting Transparent Luminescent Solar Concentrators (Advanced Optical Materials 7/2014). Issue 7 (15th July 2014) - Zhao, Yimu; Meek, Garrett A.; Levine, Benjamin G.; Lunt, Richard R.
<x xml:space="preserve">Abstract</x> A transparent luminescent solar concentrator that selectively harvests NIR photons is demonstrated. On page 606, R. R. Lunt and co‐workers describe the photophysical and electronic properties of the luminophores, the impact of ligandhost control, and the optimization of the solar concentrator architectures to realize their potential for use in electronic displays, solar windows, and other glazing systems with high defect tolerances and processability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>